2015
DOI: 10.1039/c4ra11335g
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the affinity of 2′-O-Me-oligonucleotides for complementary RNA by incorporating a stereoregulated boranophosphate backbone

Abstract: P-stereodefined boranophosphate 2′-O-Me-oligoribonucleotides (2′-O-Me-PB-ORNs) were synthesized and we revealed that an all-(Sp)-PB-backbone largely stabilized the duplex with RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Notably, ( S p)-PB/PO chimeric U 12 formed a marked stable duplex. This result agrees well with our previous report that an all-( S p)-PB 2′- O -Me decauridylate formed a more stable duplex with a complementary ORN than an unmodified counterpart, whereas the T m value of an all-( R p)-PB 2′- O -Me decauridylate and complementary ORN could not be determined owing to the instability of duplex [34]. From the observation of melting curves, it was suggested that the duplex of ( R p)-PB/PO chimeric U 12 and A 12 had a small hyperchromicity compared to the other duplexes.…”
Section: Resultssupporting
confidence: 92%
“…Notably, ( S p)-PB/PO chimeric U 12 formed a marked stable duplex. This result agrees well with our previous report that an all-( S p)-PB 2′- O -Me decauridylate formed a more stable duplex with a complementary ORN than an unmodified counterpart, whereas the T m value of an all-( R p)-PB 2′- O -Me decauridylate and complementary ORN could not be determined owing to the instability of duplex [34]. From the observation of melting curves, it was suggested that the duplex of ( R p)-PB/PO chimeric U 12 and A 12 had a small hyperchromicity compared to the other duplexes.…”
Section: Resultssupporting
confidence: 92%
“… , In this approach, the boronating reaction can be conducted after all of the base-protecting groups are removed, different from the conventional phosphoramidite method. Unprotected nucleobases were previously demonstrated not to cause any side reactions in the coupling reaction. The strategy worked to some extent and homo-T and 2′-OMe-modified homo-rU 12mers, and PB-dCAGT (4mer) could be synthesized in a stereocontrolled manner. ,, However, the coupling efficiency was not enough to synthesize nucleic acid oligomers with all four nucleobases longer than 4mer by this strategy. One probable reason for the low coupling efficiency is that the steric hindrance of both protecting groups on nucleobases and substituents on the oxazaphospholidine ring is larger than that of the conventional oxazaphospholidine approach.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed a method for synthesizing stereocontrolled P -chiral oligonucleotides using nucleoside 3′- O -oxazaphos­pholidine derivatives as monomers (the oxazaphos­pholidine method) . The oxazaphos­pholidine monomers can be stereoselectively synthesized from enantiopure 1,2-amino alcohols as chiral auxiliaries with d.r.…”
Section: Introductionmentioning
confidence: 99%